A Smarter Choice? Exploring the Behaviour Change Agenda for Environmentally Sustainable Mobility. (February 2014) - Barr, Stewart; Prillwitz, Jan
This paper explores some of the limitations of individualistic approaches towards the study and promotion of environmentally sustainable practices within the context of efforts by states to tackle global climate change. Using the example of government attempts to promote sustainable mobility through behavioural shifts amongst citizens in the UK, the paper argues that an overreliance on individualistic approaches poses three major challenges through the ways in which: (1) mobility is intricately entwined with social practices and consumption settings; (2) practices of (un)sustainable mobility are related to the structure and organisation of physical environments; and (3) solutions for sustainable mobility are framed through narrow political lenses that fail to address the potential social transformations needed to tackle climate change. Accordingly, the paper argues that both researchers and policy makers need to revisit the assumptions made concerning the role of individuals and their relationship to underlying sociostructural and political challenges for reducing carbon emissions from transport.